Broadband Polarization Splitter-Rotator and the Application in WDM Receiver - Yingxuan Zhao; Chao Qiu; Aimin Wu; Haiyang Huang; Jun Li; Zhen Sheng; Wei Li; Xi Wang; Fuwan Gan (IEEE Photonics Journal, 2019)
Polarization sensitivity is a severe problem in photonic integration devices and chips based on the high-index contrast Si/SiO2 system. In this paper, a broadband silicon polarization splitter-rotator (PSR) comprised of a bi-level taper and a counter-tapered coupler is proposed with a large fabrication tolerance. The measured insertion loss is lower than 0.7 dB/0.73 dB for the wavelength range from 1470 to 1580 nm with a crosstalk lower than −12.1 dB/−14.7 dB for TE and TM polarization input, respectively. By integrating the PSR with silicon arrayed waveguide gratings and germanium photodetectors (PDs) on a single chip, a polarization-insensitive wavelength-division-multiplexing (WDM) receiver is demonstrated with a polarization-dependent loss as low as 1.21 dB. High-speed operations are also achieved with clear eyes at 10 Gb/s.